Analisis dan Rancangan Pekerjaan - Saripa Aini; Hendra Riofita (Universitas 45 Surabaya, 2025)
Job analysis is a process of finding out information on each job or position that is needed to achieve company goals. Job analysis itself is carried out to identify the functions of a job through procedures that are required as requirements for a worker to do their job. Literature review is a description of theories, findings and other research materials obtained from reference materials to be used as a basis for research activities to develop a clear framework for formulating the problem you want to research. Job analysis at an automotive company like Honda involves an in-depth process of understanding the various roles that exist within the organization, from factories to management positions at headquarters. Honda, as one of the largest global automotive manufacturers, requires a workforce with a variety of technical and non-technical skills to support its production operations, research and development, as well as sales and service. Job analysis at Honda allows the company to determine the requirements and qualifications for each role, ultimately supporting successful, efficient business operations.